PENGARUH BRAND IMAGE, HARGA, WORD OF MOUTH DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA FRANCE BAKERY - Kristian Sinaga, Fransiskus Agus; Pristiyono; Nasution, Meisya Fitri (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2023)
This study aims to evaluate the influence of brand image, price, word of mouth, and product quality on purchasing decisions at France Bakery. This study focuses on consumers who buy products from French Bakery in the Rantau Prapat area. This study involved 200 participants and analyzed 5 factors from 24 indicators. This research uses a descriptive research design with quantitative methodology, using incidental sampling techniques. Data analysis uses SmartPLS 4.0 software, using brand image, price, word of mouth, and product quality as independent variables, while purchasing decisions are dependent variables. The results of this study indicate that brand image does not affect purchasing decisions. In addition, price, word of mouth, and product quality affect purchasing decisions.